Rawls on the embedded self: Liberalism as an affective regime. (April 2015) - Banerjee, Kiran; Bercuson, Jeffrey
In recent years, political theorists have come to recognize the central role of affect in social and political life. A host of scholars, coming from a number of distinct traditions, have variously drawn our attention to the importance of the emotions to the tradition of the history of political thought, as well as to normative political theory. This attentiveness to affect is often cast as a break with earlier, Enlightenment-inspired liberal approaches towards politics, approaches that marginalized the emotions, dismissing the passions as potentially dangerous, or neglected them altogether. According to the conventional liberal view, emotions are said to have no place in the public sphere, while proceduralist institutions abstract away from citizens' affective attachments, now cast as private preferences of individuals qua citizens. In this paper we challenge this prevalent view. We argue that no less a liberal theorist than John Rawls is deeply attentive to the place of emotions in his account of liberalism. This may seem counterintuitive given that Rawls' work has been frequently criticized for epitomizing some of the deepest problems of contemporary liberal theory, as a result of the emphasis on rationalism and reasonableness in his account of liberal justice. However, against this prevalent reading, we demonstrate that Rawls is in fact highly concerned with the role of affect and presents us with an account of the embedded liberal subject. By drawing out these dimensions of Rawls' thought, we hope to contribute to upending the conventional view of liberalism as affect-blind in order to encourage a more nuanced reading of the liberal tradition.